Digestible lysine levels in pig diets containing rice sub-products regarding the finishing phase (Orinoquia, 2013)
This investigation was aimed at estimating digestible lysine level for maximum animal husbandry performance and the best characteristics regarding pigs in their grow-finishing phase fed on rice sub-product-containing rations. Forty 67.63 ± 2.53 kg Landrace x Large White x Pietrain crossbred pigs were used in a randomised complete block experimental design involving four treatments, five repeats and two animals per experimental unit. The treatments consisted of a base isoproteicisocaloricration having four L-lysine supplementation levels (0.000, 0.191, 0.382 and 0.584), resulting in rations containing0.53, 0.68, 0.83 and 0.98% digestible lysine. Lysine level had no effect on ration (energy)consumption; however, it had a quadratic effect (p
Keywords: alternative feed; yield; nutritional requirement; pig-farming